Nitrogen and phosphorus as key drivers of wheat (Triticum aestivum L.) yield in Ethiopian Highlands: evidence from a Nutrient Omission Trial - YALEMEGENA , Gete (2025)
Limited information on location-specific yield-limiting nutrients in Ethiopia hinders optimal wheat production and increases the costs associated with other nutrient applications, emphasizing the need for targeted nutrient management strategies. A field experiment was conducted on a farmer’s field in Mojana Wodera district, North Shewa zone, Ethiopia, to identify the most yield-limiting nutrients for wheat (Triticum aestivum L.) during the 2020/2021 cropping season. The treatments were NPKSZnB (All), All-B, All-Zn, All-S1 (10.5 kg.ha-1 S), All-K, All-P, All-N, recommended NP, recommended NP + S2 (30 kg.ha-1 S), and the control (no fertilizer). The experiment was laid out in a randomized complete block design, with three replications. R software was used to analyze the data. Results showed that the nutrient omission treatments affect yield. The highest grain yield (5080 kg ha-1) was obtained from the K omission treatment, while the N omission (1388 kg.ha-1) and the control (1217 kg.ha-1) had the lowest recorded yield. In this study, N omission resulted in a severe yield reduction (73.6 % yield reduction), followed by P (22 % yield reduction) over the positive control (recommended NP). Overall, omitting N and P leads to a significant yield penalty, while wheat grain yield did not respond to the application of K, S, Zn, and B, nutrients. Therefore, more research or emphasis should be given to determining N and P nutrient rates for wheat productivity.